Replanning of BC-7 belt conveyor in coal handling system with capacity of 150 tph at Lombok ftp-2 (2x50mw) power plant - Suhariyanto; Liza Rusdiyana; Mahirul Mursid; Budi Luwar Sanyoto; Berlian Putri Fahmiliana (Jurnal Nasional Aplikasi Mekatronika, Otomasi dan Robot Industri (AMORI), 2025)
Lombok has high tourism potential that requires a reliable electricity supply, one of which comes from the Lombok FTP-2 2Å~50 MW Power Plant in Sambelia, East Lombok. This power plant uses coal supplied through a Coal Handling system, with Belt Conveyor BC-7 as one of its main components. This study aims to redesign the BC-7 Belt Conveyor with a capacity of 150 TPH through manual calculations of capacity and motor power and using Helix Delta T-6 Conveyor Design software. The study focuses on one conveyor unit, using coal material, and only discusses aspects of capacity and motor power under stable operating conditions. The methods used include literature studies, field observations, and data collection from the Lombok FTP-2 PLTU. The data was then processed for manual calculations and software simulations. The results showed a transport capacity of 165 tons/hour (a 10% increase from the previous capacity). The highest motor power without SF from the software was 8.49 kW (19.75% greater than the manual result). The use of software proved to be more efficient and helpful in planning belt conveyor systems.